Parallel Grammar Documentation in Four Talodi Languages - Norton, Russel (AAeO - Afrikanistik-Aegyptologie-Online, 2018)
This paper reports on a comparative survey of the main parts of speech (nouns, verbs, adjectives, demonstratives, pronouns, adverbs) and basic clause types of the Lumun, Tocho, Acheron, Dagik languages of Sudan, collected in parallel in a discovery workshop setting. Overall word order type is assessed, a list of diagnostic grammatical properties of Talodi languages is proposed, and the relative clustering of the four languages within the Talodi group is evaluated.